1997
DOI: 10.1159/000217464
|View full text |Cite
|
Sign up to set email alerts
|

No Coagulation Disorders under High-Dose Volume Therapy with Low-Molecular-Weight Hydroxyethyl Starch

Abstract: Hydroxyethyl starch (HES) is often used for volume therapy. Since bleeding complications have been reported repeatedly, a strict dose limitation of a maximum of 1,500 ml 6% solution per day is recommended. However, many indications require higher dosages. Bleeding complications are known to be caused by an acquired von Willebrand syndrome. It has been shown that the accumulation of large molecules and their impairment in the coagulation system can be avoided by using HES preparations with a low in vivo molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…Although HES may influence blood coagulation, its safe use during intracranial procedures has been demonstrated 21. Since 2003, a different formula of HES with less affect on coagulation was used 16.…”
Section: Resultsmentioning
confidence: 99%
“…Although HES may influence blood coagulation, its safe use during intracranial procedures has been demonstrated 21. Since 2003, a different formula of HES with less affect on coagulation was used 16.…”
Section: Resultsmentioning
confidence: 99%
“…Low-molecular-weight hydroxyethyl starch may be better than its high-molecular-weight counterpart, which has antiplatelet properties and adverse effects on coagulation. 5 Mackenzie et al 6 reported using a hemoglobin-based acellular oxygen-carrying solution (HBOC-201) in a Jehovah's Witness with traumatic hemorrhagic shock when the patient's hemoglobin level reached a low of 4.5 mg/dL;…”
Section: Volume Replacementmentioning
confidence: 99%
“…Thus, in cardiac surgery studies with albumin as the control, HES has resulted in platelet depletion and dysfunction, prothrombin time and activated partial thromboplastin time prolongation, and increased postoperative bleeding. ‡ One NCT of 444 patients revealed significant increases in blood product use, as well as postoperative blood loss, in patients receiving HES †References 27,29,34,40,61,62,69,78,80,82,94,103,104. ‡References 3,11,13,15,17,46,48,50,65,92.…”
Section: Coagulopathymentioning
confidence: 99%